2005
DOI: 10.1111/j.1365-2125.2005.02431.x
|View full text |Cite
|
Sign up to set email alerts
|

Ziprasidone decreases cortisol excretion in healthy subjects

Abstract: Br J Clin Pharmacol AimsTo determine the influence of the atypical antipsychotic ziprasidone on cortisol excretion. MethodsIn a double-blind, placebo-controlled, randomized cross-over design 11 healthy male subjects were studied twice for 2 consecutive nights (N1, undisturbed sleep conditions; N2, exposure to acoustic stress) 5 days apart. Placebo or ziprasidone 40 mg was administered orally 2 h before bedtime on N1 and N2. Urine was collected during three fractionated collection periods (evening; night; morni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Regarding these data, one may conclude that antagonism of central 5‐HT 2A/C and/or histamine H 1 receptors is responsible for the acute inhibitory effects of mirtazapine on cortisol and ACTH secretion in healthy volunteers. This assumption is further corroborated by the finding that atypical antipsychotics with 5‐HT 2 ‐ and H 1 ‐blocking properties, such as quetiapine (135–137), olanzapine (136) or ziprasidone (138), but not the classical dopamine D 2 ‐antagonist haloperidol (70, 136) have also been demonstrated to acutely inhibit cortisol secretion in healthy subjects.…”
Section: Mirtazapine Challenge and Hpa Axis Activity In Healthy Subjectsmentioning
confidence: 73%
“…Regarding these data, one may conclude that antagonism of central 5‐HT 2A/C and/or histamine H 1 receptors is responsible for the acute inhibitory effects of mirtazapine on cortisol and ACTH secretion in healthy volunteers. This assumption is further corroborated by the finding that atypical antipsychotics with 5‐HT 2 ‐ and H 1 ‐blocking properties, such as quetiapine (135–137), olanzapine (136) or ziprasidone (138), but not the classical dopamine D 2 ‐antagonist haloperidol (70, 136) have also been demonstrated to acutely inhibit cortisol secretion in healthy subjects.…”
Section: Mirtazapine Challenge and Hpa Axis Activity In Healthy Subjectsmentioning
confidence: 73%
“…There is a case study that reported elevated PRL levels after 9 days of ziprasidone administration (80 mg/day) (257,258). Moreover, other studies have shown that ziprasidone suppresses the activity of the HPA-axis (n = 11, healthy volunteers; 40 mg/day), reducing the levels of nocturnal cortisol excretion, likely due to its antagonism toward H1 and α1 adrenergic receptors (259). Studies on the adverse effects produced by ziprasidone are scarce and more research is needed.…”
Section: Ziprasidonementioning
confidence: 99%
“…The administration of ziprasidone and quetia- pine decreases the urinary cortisol excretion in healthy subjects [22,46] . Olanzapine also reduces the ACTH and cortisol secretion in healthy subjects, whereas haloperidol has no such affect.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, CRF is a regulatory factor in HPA axis activity and in the pathophysiology of depression and anxiety. In healthy subjects, ziprasidone decreased cortisol excretion [22] . However, no study has examined the effects of ziprasidone on stress-induced CRF.…”
Section: Introductionmentioning
confidence: 99%